Thymol in fattening rabbit diet, its bioavailability and effects on intestinal morphology, microbiota from caecal content and immunity. Issue 2 (22nd June 2021) - Placha, Iveta; Bacova, Kristina; Zitterl‐Eglseer, Karin; Laukova, Andrea; Chrastinova, Lubica; Madarova, Michaela; Zitnan, Rudolf; Strkolcova, Gabriela
Abstract: To our knowledge, no study has been carried out to evaluate the effects of thymol sustained administration on gut health and immune response in terms of its bioavailability in the rabbit organism. A total of 48 rabbits were randomly divided at 35 days of age into two dietary treatment groups (C/control or T/thymol at 0.025% addition). Thymol was added for 21 days and then withdrawn for 7 days. Thymol content in faeces ( p  < 0.001) and caecal content ( p  < 0.05) was significantly higher than in plasma during the thymol addition and withdrawal (2442 ± 451.4, 881.9 ± 231.3 ng/g DM and 46.2 ± 28.4 ng/ml, respectively; 149.5 ± 40.54, 45.76 ± 12.44 ng/g DM and 2.73 ± 0.45 ng/ml, respectively). Increasing of villi height to crypt depth ratio in small intestinal wall ( p  < 0.01), phagocytic activity in blood ( p  < 0.0001) and lactic acid bacteria in caecal appendix ( p  < 0.01) and faeces ( p  < 0.05) was still presented after withdrawn of thymol. The thymol at this concentration demonstrated its biological properties and was able to positively affect gut health and immune response of rabbits.